A Chromosome-Level Genome Assembly of the Reed Warbler (Acrocephalus scirpaceus). (9th September 2021) - Sætre, Camilla Lo Cascio; Eroukhmanoff, Fabrice; Rönkä, Katja; Kluen, Edward; Thorogood, Rose; Torrance, James; Tracey, Alan; Chow, William; Pelan, Sarah; Howe, Kerstin; Jakobsen, Kjetill S; Tørresen, Ole K
Abstract: The reed warbler ( Acrocephalus scirpaceus ) is a long-distance migrant passerine with a wide distribution across Eurasia. This species has fascinated researchers for decades, especially its role as host of a brood parasite, and its capacity for rapid phenotypic change in the face of climate change. Currently, it is expanding its range northwards in Europe, and is altering its migratory behavior in certain areas. Thus, there is great potential to discover signs of recent evolution and its impact on the genomic composition of the reed warbler. Here, we present a high-quality reference genome for the reed warbler, based on PacBio, 10×, and Hi-C sequencing. The genome has an assembly size of 1, 075, 083, 815 bp with a scaffold N50 of 74, 438, 198 bp and a contig N50 of 12, 742, 779 bp. BUSCO analysis using aves_odb10 as a model showed that 95.7% of BUSCO genes were complete. We found unequivocal evidence of two separate macrochromosomal fusions in the reed warbler genome, in addition to the previously identified fusion between chromosome Z and a part of chromosome 4A in the Sylvioidea superfamily. We annotated 14, 645 protein-coding genes, and a BUSCO analysis of the protein sequences indicated 97.5% completeness. This reference genome will serve as an important resource, and will provide new insights into the genomic effects of evolutionary drivers such as coevolution, range expansion, and adaptations to climate change, as well as chromosomal rearrangements in birds.